Crystal structure of 2-[1-(4-bromobenzyl)-1H-1, 2, 3-triazol-4-yl]methoxynaphthalene-1, 4-dione. (April 2015) - Raja, Rajamani; Kandhasamy, Subramani; Perumal, Paramasivam T.; SubbiahPandi, A.
No abstract available